TERAPI SULIH (SWITCH THERAPY) ANTIBIOTIK PADA PASIEN PNEUMONIA KOMUNITI DI RSUD WANGAYA KOTA DENPASAR - Dewi Puspita Apsari; Ni Made Krisna Dwiyanti; I.B.N. Maharjana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Hospitalized community-acquired pneumonia (CAP) patients are always prescribed intravenous (IV) antibiotics. Inappropriate and unnecessary IV antibiotics usage leads to an increase in healthcare costs and bacterial resistance. IV to per oral (PO) conversion therapy can overcome these problems. The aim of the study was to evaluate the practice of switching from intravenous to oral antibiotics of inpatients with community-acquired pneumonia (CAP). This retrospective observational study was conducted by taking patient medical record from january until december 2019. Outcomes of the study are patient characteristics, pattern use, antibiotic and type conversion therapy. Adult inpatients on conversion therapy were eligible for study enrollment. Data were analyzed descriptively using SPSS 17.0. The study showed that among 78 patients who were eligible for conversion therapy. Most of the patient has mean duration conversion therapy 48-72 hours as much as 55 (70,5%). Beta-lactams were the most commonly converted antibiotics. However, the step-down therapy was the major type of conversion practiced in this study as much as 48 (61,5) followed by sequential and switch over with numbers 21 (27%) and 9 (11,5%) respectively. Based on the study findings wangaya hospital should improve the practice of sequential therapy in order to reduce the burden of CAP.